Prosecuting piracy: the need for legislative measures / Ahmad Ismail Illman, Syed Naqiuddin Shahab and Syed Adam Al-Aqib - Illman, Ahmad Ismail; Shahab, Syed Naqiuddin; Al-Aqib, Syed Adam (2012)
"Prosecuting Piracy: The Need for Legislative Measures", is a legal study on the lack of domestic legal framework pertaining to piracy in Malaysia and how to overcome and enhance the legal framework to combat piracy. Piracy is regarded as Hostis Humani Generis, which means the enemy of mankind. Piracy by law of nations is sui generis. It is an offence against the law of nations, whom any nation may in the interest of all capture and punish. Therefore, there is a strict adherence to the law that needs to be studied in order capture and punish the pirates. Since, Malaysia had ratified United Nations Convention on Laws of the Sea 1982 (UNCLOS) Malaysia is under an obligation to make necessary modification in its legislation to ensure the fulfillment of the obligation undertaken when they sign the treaty of UNCLOS. This research is a humble attempt to address the need to have a specific domestic law to prosecute piracy in the Malaysian Courts with the hope that it may act as a deterrent to solve the never ending piratical attacks against Malaysian vessels and enhance the maritime enforcement law in Malaysia. This may be done by adopting UNCLOS into our domestic legal framework via doctrine of transformation, which incorporates international treaty into the domestic legal system. Doctrine of transformation allows the treaty to be adapted to the needs of Malaysia.